2018
DOI: 10.1080/02699052.2018.1430376
|View full text |Cite|
|
Sign up to set email alerts
|

Neurophysiological and cognitive impairment following repeated sports concussion injuries in retired professional rugby league players

Abstract: These findings of motor and cognitive changes, along with neurophysiological alterations, particularly with intracortical inhibition, nearly two decades post-concussion provides evidence for long-term sequelae for athletes with a history of repeated head trauma in contact sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 71 publications
2
64
1
Order By: Relevance
“…Categories were created to differentiate between concussion injury and recovery, as seen in short term studies [11]. Conversely long-term studies sort to understanding the physiology of persistent post-concussion symptoms [62], or the physiology of those with chronic changes years or decades later [63][64][65].…”
Section: Allocation Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Categories were created to differentiate between concussion injury and recovery, as seen in short term studies [11]. Conversely long-term studies sort to understanding the physiology of persistent post-concussion symptoms [62], or the physiology of those with chronic changes years or decades later [63][64][65].…”
Section: Allocation Of Studiesmentioning
confidence: 99%
“…MT data was presented in eight studies [24,58,63,64,[74][75][76][77] with only one study reporting significantly increased MT in both symptomatic and asymptomatic concussed groups, compared to control [56]. Three studies reported latency data, with no difference between groups [65,74,78]. MEP amplitude presented in eight studies [24, 62-65, 74, 76] showed no differences between groups.…”
Section: Long-term Tms Concussion Studiesmentioning
confidence: 99%
See 3 more Smart Citations